Utilization of blood cultures in Danish hospitals: a population-based descriptive analysis. (April 2015) - Gubbels, S.; Nielsen, J.; Voldstedlund, M.; Kristensen, B.; Schønheyder, H.C.; Vandenbroucke-Grauls, C.M.J.E.; Arpi, M.; Björnsdóttir, M.K.; Knudsen, J. Dahl; Dessau, R.B.; Jensen, T. Gorm; Kjældgaard, P.; et al.
Abstract: This national population-based study was conducted as part of the development of a national automated surveillance system for hospital-acquired bacteraemia and ascertains the utilization of blood cultures (BCs). A primary objective was to understand how local differences may affect interpretation of nationwide surveillance for bacteraemia. From the Danish Microbiology Database, we retrieved all BCs taken between 2010 and 2013 and linked these to admission data from the National Patient Registry. In total, 4 587 295 admissions were registered, and in 11%, at least one BC was taken. Almost 50% of BCs were taken at admission. The chance of having a BC taken declined over the next days but increased after 4 days of admission. Data linkage identified 876 290 days on which at least one BC was taken; 6.4% yielded positive results. Ten species, Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Streptococcus pneumoniae, Enterococcus faecium, Enterococcus faecalis, Pseudomonas aeruginosa, Candida albicans, Enterobacter cloacae and Klebsiella oxytoca, accounted for 74.7% of agents for this purpose classified as pathogenic. An increase in BCs and positive BCs was observed over time, particularly among older patients. BCs showed a seasonal pattern overall and for S. pneumoniae particularly. A predominance of male patients was seen for bacteraemias due to S. aureus, E. faecium and K. pneumoniae. Minor differences in BCs and positive BCs between departments of clinical microbiology underpin the rationale of a future automated surveillance for bacteraemia. The study also provides important knowledge for interpretation of surveillance of invasive infections more generally.